Levan in the developing of new colon-specific polymer material: evaluation of the permeability, moisture and thermal analyses in free films of Eudragit® FS 30 D - doi 10.4025/actascihealthsci.v34i2.11729 (Acta Scientiarum. Health Sciences, 2012)
Levan was used as agent in the synthesis of new colon-specific polymeric matrix together with Eudragit® FS 30 D. Eudragit® FS 30 D films incorporated with levan were made by casting process and characterized to: water vapour transmission, sweeling index, differential scanning calorimetry and thermogravimetric. The levan increased the films permeability (p < 0.001) however did not influenced in the sweeling index of the formulations (p > 0.05). The thermal analyses of the films indicated a glass transition temperature approximate at 47°C and thermal decomposition at 400°C. The results indicated that there is potential for using such site-specificity blend as pharmaceutical coating material.